C19MOOC: A Remote Learning Reference Framework for Science and Technology Education - Saikat S.; Dhillon J.S.; Alias R.; Fatima M.A. (MDPI, 2023)
With the coronavirus disease 2019 (COVID-19) pandemic, education and learning have been compelled to go entirely online rather than using conventional offline media. As a result, remote learning adoption has exploded, neither planned nor anticipated. The challenges and benefits of such widespread adoption have gradually unfolded in front of our own eyes. Unlike other courses, science and technology (S&T) courses are more technical, involve practical lessons, and require careful planning for effective delivery via remote learning platforms. Thus, existing remote learning frameworks are too general and are not designed for S&T courses. In addition, the evolving requirements of learners demand revision of prior frameworks to be relevant today. In this paper, we propose a remote learning reference framework called C19MOOC for S&T courses offered at higher learning institutions. The framework will provide the essential components to be considered in the development of remote learning systems for these courses. A focus group discussion was conducted to elicit learners requirements and preferences for remote learning systems that offer S&T courses. The existing Massive Open Online Course (MOOC) framework was adapted to match learners current needs and expectations. The MOOC frameworks existing dimensions and components were redefined, and three new dimensions (Engagement, Governance, and Self-determination) and components were added. An expert review was administered to validate the C19MOOC framework. Based on our findings, it was determined that remote learning has excellent potential as an effective platform for education at higher learning institutions. Shortcomings that emerged during its immense use in the period of the COVID-19 pandemic can be addressed by leveraging the proposed framework. The C19MOOC framework will be useful for S&T education stakeholders, institutions, and system developers to identify suitable dimensions, components, and features to consider when designing remote learning systems for S&T education. 2022 by the authors.